Tourism demand forecasting - a review on the variables and models - Sarah, Mohd Khaidi; Noratikah, Abu; Noryanti, Muhammad (IOP Publishing, 2019)
Alongside with the growth of the tourism industry, researchers took advantage to conduct numerous studies in forecasting of tourism demand. The objective of this paper is to review the studies on tourism demand starting from 2010 to 2018 which varies on the independent variable such as tourist income, exchange rate, gross domestic product, and others. Besides, this study will focus on the models used to forecast and analyse tourism demand which are time-series model, economic causal model and artificial intelligence model. The result from this review shows it is difficult to conclude which models performed the best for tourism demand. However, it is worth to mention that combined models outperformed single model in most of the studies. Furthermore, the authors mentioned about the roles of tourism practitioners in the industry, tourism seasonality and suggestions for further studies in the future.